Process Innovation and its Impacts on MSMEs Resilience in Ghana: The Moderating Role of Enterprise Risk Management - Nkansah, Obed Kwabina Opoku; Gaffar, Vanessa; Sofia, Alfira; Heryana, Tony (Image : Jurnal Riset Manajemen, 2024)
Firms’ resilience is of key interest to practitioners, owing to the fact that in most developing countries including Ghana, over 60 percent MSMEs do not survive the first five years of business operations. This study looks at how enterprise risk management may influence the impact of process innovation practices of Lean Six Sigma and Quality management Systems on MSMEs' resilience. The study used a quantitative research design, collecting survey data via Google Forms from a sample of 356 MSMEs and analysing it using SPSS software. The results indicated that MSMEs' resilience can be positively impacted by Lean Six Sigma practices. On the other hand, Quality management Systems could negatively affect the resilience of firms. Again, the research illustrates that enterprise risk management practices enhance the impact of process innovation practices on firms’ resilience. Specifically, the findings showcase the importance of utilizing process innovation practices and risk management as key principles in obtaining resilient MSMEs. Implications of these findings are important for managers of MSMEs, policy makers and researchers.